Comparison of The Delta Robot ABB IRB 360 Properties After Collisions - Semjon, Jan; Sukop, Marek; Vagas, Marek; Janos, Rudolf; Tuleja, Peter; Koukolova, Lucia; Marcinko, Peter; Jurus, Ondrej; Varga, Jozef (Communications - Scientific letters of the University of Zilina, 2018)
The use of robots with their partial damage is not common, and it is not used in safety terms. If the robot works in a controlled environment after partial damage, the robot can be used for a short period of time when the speed of moving and weight of the load are reduced. In the event of damage one of the arms of the parallel robot, the parallelism of the movable platform towards base is lost. This results in a loss of accuracy, which in the case of shortening one of the robots arms is reflected by a gradual change in the distance of the removal site from the storage site. This change is bigger with the greater distance of the center of gravity effector from the robot output flange. For the short-term unavailability of replacement arms, it was decided to continue the training with the robot with rebuilt and reinforced arm. This article concerned with performing a control measurement to detect the deviation value that could be compensated in the execution of the individual cycles of the robot. The measurement compared values of pose accuracy and pose repeatability of the robot after damage by using measured compensated deviations.